Intelligent Tutoring for Hadith: Evaluating ChatGPT-Enhanced Pedagogy in Islamic Higher Education - Abdulghani, Naser Ali; Touré, Youcha Alassane (Indonesian Journal of Islamic Education Studies (INJURIES), 2025)
This study examines the integration of ChatGPT as an intelligent tutoring tool in the teaching of Hadith to undergraduate Islamic studies students at the University of Benghazi. By employing a mixed-methods design, the research involved 25 participants over four weeks of structured Hadith study using ChatGPT. Quantitative results demonstrated significant improvements in learning outcomes, with average scores increasing from 56.7 on the pre-test to 73.2 on the post-test, representing a mean gain of 16.5 points (p< .001, Cohen’s d = 1.45). Qualitative analysis of interviews and reflective journals revealed that students valued ChatGPT for enhancing comprehension, providing personalized explanations, and fostering motivation. At the same time, concerns emerged regarding the accuracy of responses and the potential for over-reliance on AI, underscoring the importance of teacher mediation. The integration of findings highlights that ChatGPT functions most effectively as a supplementary cognitive and motivational tool rather than a replacement for scholarly guidance. The study contributes to growing literature on AI in education by extending its application to religious studies, specifically Hadith pedagogy, and offers broader implications for Islamic higher education. Findings suggest that AI can facilitate access to knowledge, but careful implementation is required to safeguard authenticity and critical engagement.